Positive selection drives the evolution of a primate bitter taste receptor gene. Issue 10 (23rd March 2021) - Dong, Xiaoyan; Liang, Qiufang; Li, Jiaping; Feng, Ping
Abstract: Bitter taste perception is important in food choice of animals, and it is mediated by bitter taste receptor (T2R) containing three regions: extracellular regions (ECs), transmembrane regions (TMs), and intracellular regions (ICs). It is hypothesized that ECs, TMs, and ICs are under different selective pressures, with ECs being unstable while TMs and ICs being constrained. To test this hypothesis, we examined the selective pressures on one of the bitter taste receptor genes‐ T2R1 and its different areas from 35 primates and found that T2R1 was under neutral evolution but with some positively selected sites in it. Further analyses suggested that TMs, ICs, and the concatenated transmembrane region TM1237 were under purifying selection; in contrast, extracellular regions, the first and second extracellular loop (EL1, EL2), were subject to positive selection with several positively selected sites in them. Therefore, this study supported the above‐mentioned hypothesis. The reason why EL1 and EL2 of T2R1 have positively selected sites is probably due to their participation in forming the cap‐like structure involved in ligand binding. Positive selection acts as a driving force of the T2R1 functional differentiation and confers the ability to discern various bitter substances for primates, which could help them to adapt to the changing environment during the evolutionary course. Abstract : Positive selection acts as a driving force of the T2R1 functional differentiation and confers the ability to discern various bitter substances for primate, which could help them to adapt to the changing environment during the evolutionary course.